Konteks berteologi di Indonesia : buku penghormatan untuk HUT ke 70 Prof. Dr. P.D. Latuihamallo - Konteks... (BPK Gunung Mulia, 1997)
budi, c.1/oen, c2/ast c.3/ir,c.4-5/,ws.perbaikan/en, c.6/stoc7, c.1-6